Beyond the numbers—understanding women's experiences of accessing care for abnormal uterine bleeding (AUB): a qualitative study. Issue 11 (17th November 2020) - Henry, Claire; Jefferies, Regina; Ekeroma, Alec; Filoche, Sara
Abstract : Objective: To gain a deeper understanding of women's experiences of accessing care for abnormal uterine bleeding (AUB) in order to inform future strategies to improve care pathways, including the early detection of endometrial cancer. Design: We conducted semistructured interviews with 15 women who attended their first gynaecological specialist consultation for AUB at Wellington Regional Hospital between October and December 2019. Inductive thematic analysis was used to explore experiences and barriers to seeking care. Results: The median age of the participant cohort was 45 years, with women self-identifying as New Zealand European (9/15), Māori (2/15) and Pasifika (4/15). All women had sought investigation for their AUB in primary care, for some women this was over a timeframe of many years. For all women, AUB had a significant and traumatic impact on their quality of life including their relationships and their work or education. Women described how they felt they often received inadequate care for AUB, and reported negative experiences with their general practitioner. Timely access was further compounded by feelings of embarrassment and that AUB was a taboo subject, and being able to discuss it with family, friends and their general practitioners was difficult. Conclusion: Women in our cohort experienced a multitude of compounding influences that acted as barriers to them having access to appropriate and timely care. Information campaigns that create awareness around 'abnormal periods' alongside better health provider practice guidelines for AUB investigation need to be a priority.